Determinants of Lecturer Innovativeness in Higher Education: A PRISMA-Based Systematic Literature Review of Information Technology Literacy, Self-Efficacy, Achievement Motivation, and Knowledge Management - Maryani, Novi; Hardienata, Soewarto; Suherman, Irman (Educational Researcher Journal, 2026)
Lecturer innovation is a strategic factor in improving the quality of learning, research productivity, and competitiveness of higher education institutions in the era of digital transformation. However, empirical studies on the determinants of lecturer innovation are still scattered and have not been comprehensively integrated. This study aims to systematically synthesize international literature on the role of information technology (IT) literacy, self-efficacy, achievement motivation, and knowledge management in enhancing lecturer innovation. The study used a Systematic Literature Review (SLR) approach with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Articles were obtained from the Scopus database for the period 2010–2025. After going through the processes of identification, screening, eligibility, and inclusion, a total of 46 empirical articles were analyzed thematically. The results of the study indicate that IT literacy increases the capacity for digital pedagogical innovation; self-efficacy strengthens the courage to experiment and adapt to change; achievement motivation encourages innovative performance orientation; while knowledge management acts as an institutional reinforcement that integrates individual innovation into the organizational system. This study produces an integrative conceptual framework that positions knowledge management as a structural enabler and psychological factors as proximal drivers of lecturer innovation. These findings provide theoretical contributions and strategic implications for the development of higher education policies based on sustainable innovation.